THE VALIDITY OF ISLAMIC BALANCES OF REGIONAL REGULATION (PERDA) IN INDONESIA’S CONSTITUTIONAL PERSPECTIVE: Indonesian Political Law to the Post Amendment Constitution of Republic of Indonesia of 1945 - Santing, Waspada S (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2019)
Islamic-based laws have a strong historical roots in Indonesia society. Culturally-based rules of Islam always flourish accompanying the history of nation’s journey intertwined with the dynamics of community life. Those historical values are embodied in such a firm and clear in the philosophy and principles of the country: Pancasila and the 1945 Constitution. Therefore, the establishment, construction, and development of Islamic-based Regulations, has a constitutional foundation for formal law as enacted, either at the national or regional law order.